The Late Variscan control on the location and asymmetry of the Upper Rhine Graben - Grimmer, Jens Carsten; Ritter, Joachim R. R.; Eisbacher, Gerhard H.; Fielitz, Werner (International journal of earth sciences, 2017)
The NNE-trending Upper Rhine Graben (URG) of the European Cenozoic Rift System developed from c. 47 Ma onwards in response to changing lithospheric stresses in the northwestern foreland of the Alps. The composite graben structure consists of three segments, each c. 100 km long and 30-40 km wide, but flares to c. 60 km near its southern and to c. 80 km near its northern termination. Normal faulting induced a total extension of 5-8 km of the 1-2 km thick Mesozoic sedimentary Franconian platform and underlying Variscan basement rocks. However, distribution of an up to 3.5 km thick sedimentary graben fill and cumulative displacements near Eastern and Western Main Border fault systems suggest that subsidence of the graben floor and shoulder uplift created strong cross-sectional asymmetries. Cumulative W-down displacements >3 km along strongly segmented transfer faults in the east contrast with E-down displacements <3 km and major monoclinal “block fields” in the west. Both location and asymmetry of the URG appear to be related to lithospheric shear zones that originated within the central parts of the Variscan orogen between c. 330 and 315 Ma. Following pervasive deformation, HT/LP regional metamorphism and emplacement of granodioritic-granitic plutons a c. 50-km-thick orogenic crust were thinned to an about 30-km-thick two-layered crust above a reconsolidated and relatively planar crust-mantle boundary (Moho). In the URG area extensional thinning of the crust appears to have occurred mainly along a composite NNE-striking and mainly W-down “East Rhine Detachment”, which is partly exposed along the Wehratal, Omerskopf, Otzberg and other mylonitic-cataclastic shear zones in the basement of the eastern graben shoulder. These shear zones probably extend into lower crustal levels, where they are revealed as gently W-dipping seismic reflectors beneath and west of the URG. Major W-down displacements probably account for the mapped abundance of high-grade metamorphic basement rocks on the eastern graben shoulder in contrast to the predominantly low-grade metamorphic to unmetamorphosed sedimentary-volcanic rocks exposed on the western shoulder. Although between c. 310 and 270 Ma NE-trending Permocarboniferous volcanic-sedimentary basins of the URG area subsided along upper crustal faults that mimic the trend of Variscan faults, initial broad lithospheric cooling from c. 270-200 Ma led to subsidence of a distinctly NNE- to SSW-oriented embayment that was probably underlain by thinner Palaeozoic crust in the area of the NNE-trending East Rhine Detachment. After re-emergence of the platform above sea level in late Mesozoic times, the deep-reaching W-dipping “extensional defects” of the East Rhine Detachment exerted a primary lithospheric scale control on both location and cross-sectional asymmetry of the Cenozoic graben structure. NE- and NW-striking, strongly altered and more shallow rooted Permocarboniferous or Mesozoic faults exerted secondary upper crustal controls on transfer faults and the accommodation zones near the terminations and segment boundaries of the URG. Deep crustal to upper lithospheric asymmetries continue to influence the neotectonic setting of the URG, such as westward rising earthquake hypocentres. Seismic activity along the URG appears to be part of a >600 km long zone that delimits the trailing edge of a SW-moving lithospheric block. In the URG area, NE-SW-oriented seismic anisotropy at sublithospheric depths of c. 60-80 km suggest active mantle flow in this direction as a possible driving force for the reactivation of pre-graben lithospheric shear zones.